Pelvic area, calving ease and rebreeding in first calf heifers - R.R. Schalles; A.T. Fleck; L.R. Corah; G. Kiracofe (Kansas Agricultural Experiment Station Research Reports, 1979)
Pelvic area had little influence on the number or severity of calving problems after size and condition of two-year-old first-calf heifers, sex and weight of their calf, and genetic background of the heifer and her calf were accounted for. Little difference in rebreeding was attributed to calving difficulty, although heifers that had Caesarean deliveries rebred about two weeks later than those giving natural birth.
Keywords: Cattlemen' s Day; 1979; Report of progress (Kansas State University. Agricultural Experiment Station); 350; Beef; Pelvic area; Calving ease; Rebreeding; Heifers